2019
DOI: 10.1097/brs.0000000000002898
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Hospital Resource Utilization of Staphylococcus aureus Infection Post Elective Posterior Instrumented Spinal Fusion Surgeries in U.S. Hospitals: A Retrospective Cohort Study

Abstract: Supplemental Digital Content is available in the text Using hospital discharge and microbiology data from 129 U.S. hospitals, the authors found that Staphylococcus aureus infections post elective posterior instrumented spinal fusion surgeries are associated with significantly higher hospitalization cost, length of stay, and 180-day risk of readmission compared with those with no such infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Rosenthal et al conducted a study assessing cost and hospital utilization related to postsurgical staph aureus superficial site infection (SSI) and blood stream infection (BSI) during a 180-day follow up period post elective spine fusion. 24 The study found that the rate of contracting a S. aureus during the 180-day period was 2.22%. Additionally, 96.03% of patients with invasive S. aureus infection had at least one readmission compared with 19.18% patients without S. aureus infection.…”
Section: Resultsmentioning
confidence: 96%
“…Rosenthal et al conducted a study assessing cost and hospital utilization related to postsurgical staph aureus superficial site infection (SSI) and blood stream infection (BSI) during a 180-day follow up period post elective spine fusion. 24 The study found that the rate of contracting a S. aureus during the 180-day period was 2.22%. Additionally, 96.03% of patients with invasive S. aureus infection had at least one readmission compared with 19.18% patients without S. aureus infection.…”
Section: Resultsmentioning
confidence: 96%
“…The data that support the ndings of this study are available from Premier Healthcare Solutions, Inc. (Charlotte NC), but restrictions apply to the availability of these data, which were used under license for the current study, and so are not publicly available. [2,22]. The protocol for this study was nonetheless submitted to Western IRB (Puyallup WA), which con rmed its exempt status.…”
Section: Declarationsmentioning
confidence: 99%
“…Data from the PHD are thus considered deidenti ed in accordance with the HIPAA Privacy Rule described in Title 45 of the US Code of Federal Regulations (CFR) Part 164.506(d)(2)(ii)(B) and are exempt from Institutional Review Board (IRB) oversight, as provided in 45 CFR 46.101(b)(4 [2,22]. The protocol for this study was nonetheless submitted to Western IRB (Puyallup WA), which con rmed its exempt status.…”
Section: Study Design Data Source and Participant Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical site infection (SSI) is among the most serious complications of spinal surgery in terms of the health status and clinical outcomes of patients as well as costs. 1,2 Despite prophylactic antibiotics and aseptic techniques, SSIs occur at a rate of 0.6%-11.9% in patients undergoing spinal surgery. 3−5 Given these circumstances, various attempts have been made to reduce the incidence of infections after spinal surgeries.…”
mentioning
confidence: 99%